The interaction of paragraph 12(5) of the gth schedule to the act with reference to estate planning and corporate structures - Stassen, Cecilia Jacoba (Centre for Law and Society, 2026)
Paragraph 12 of the Eighth Schedule to the Income Tax Act No. 58 of 1962 (the Act) deals with events treated as disposals and acquisition for Capital Gains Tax purposes, i.e. deemed disposals and acquisitions. This dissertation will deal with subparagraph 5 of paragraph 12 of the Eighth Schedule, in specific, which deems the reduction or waiver of debt by a creditor to be a disposal for the purposes of Capital Gains Tax. Due to the strict provisions of paragraph 12(5) it has an impact on both corporate structuring and transactions between connected persons, as well as, an influence on estate planning and the drafting of a will. Paragraph 12(5) is quite a tricky paragraph, and has led to two opposing tax court decisions dealing with the waiver of a loan to a trust through way of a bequest. Unfortunately none of the cases have progressed on appeal to the High Court and, therefore, no precedent has been set. This dissertation will firstly investigate the interaction of this paragraph with other sections in the Act in Chapter 2 and 3, as well as, the effect it has within a group structure in the corporate environment. Secondly, it will investigate the application and implication of the two tax court cases mentioned above in Chapter 4 to estate planning. Lastly, the interaction of paragraph 12(5) with suretyship agreements and its applicability where debt prescribes will be investigated in Chapter 5.